2010
DOI: 10.1152/ajpcell.00448.2009
|View full text |Cite
|
Sign up to set email alerts
|

CCK activates RhoA and Rac1 differentially through Gα13 and Gαq in mouse pancreatic acini

Abstract: Cholecystokinin (CCK) has been shown to activate RhoA and Rac1, as well as reorganize the actin cytoskeleton and, thereby, modify acinar morphology and amylase secretion in mouse pancreatic acini. The aim of the present study was to determine which heterotrimeric G proteins activate RhoA and Rac1 upon CCK stimulation. Gα13, but not Gα12, was identified in mouse pancreatic acini by RT-PCR and Western blotting. Using specific assays for RhoA and Rac1 activation, we showed that only active Gα13 activated RhoA. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 57 publications
(108 reference statements)
7
33
0
Order By: Relevance
“…In most situations, rac1 and RhoA exhibit an antagonistic relationship at multiple levels and there is balance between the activities of rac1 and RhoA (22)(23)(24)(25). This opposition can be reciprocal and unidirectional, as observed in NIH3T3 cells, in which rac1 activation induces epithelial cell morphology, including cadherin-based junctions, accompanied by decreased RhoA activity.…”
Section: Introductionmentioning
confidence: 99%
“…In most situations, rac1 and RhoA exhibit an antagonistic relationship at multiple levels and there is balance between the activities of rac1 and RhoA (22)(23)(24)(25). This opposition can be reciprocal and unidirectional, as observed in NIH3T3 cells, in which rac1 activation induces epithelial cell morphology, including cadherin-based junctions, accompanied by decreased RhoA activity.…”
Section: Introductionmentioning
confidence: 99%
“…In this study CCK was shown to rapidly increase the expression of both α12 and α13 as well as increasing the association of RhoA and Vav2 with Gα 13 but not Gα 12 . In mouse pancreas and pancreatic acini both PCR and Western blotting revealed the presence of Gα 13 but not Gα 12 (29). In accord with previous studies (1), Gα 13 was associated with a membrane fraction in both control and stimulated acini.…”
Section: Specific Function In the Pancreassupporting
confidence: 90%
“…Similar results had been reported earlier in intestinal smooth muscle cells expressing Gα13 (23) and in NIH 3T3 cells stabely transfected with CCKA receptors (19). A mutant form of p115-RGS (E29K) failed to modify CCK-induced RhoA activation (29). The effect of p115-RGS expression was shown to be specific for G 12/13 signaling as it had no effect on Ca 2+ mobilization or cAMP formation.…”
Section: Specific Function In the Pancreassupporting
confidence: 88%
See 2 more Smart Citations